Design and synthesis of 2-amino-thiophene-tethered ureidopenicillin analogs with potentantibacterial and antitubercular activity - Wagh, Mahendra A.; Baravkar, Sachin B.; Jedhe, Ganesh S.; Borkute, Rachna; Choudhari, Amit S.; Sarkar, Dhiman; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
Ureidopenicillins are a class of penicillins which are antibiotics active against gram-negative bacteria. Herein, we report the synthesis of 2-aminothiophene-tethered ureidopenicillin analogues and their in vitro antibacterial and antitubercular activity. Intriguingly, unlike the reported ureidopenicillins which are active against gram-negative bacteria, the synthesised 2-aminothiophene-tethered ureidopenicillins were significantly active against Gram-positive bacterial strains and showed moderate inhibition towards gram-negative bacterial strains. Among all the analogs, compound 1b containing 2-aminothiophene moiety with minimum inhibitory concentration (MIC): 0.29, 0.32, > 10, > 10 mg/ml for Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa, respectively, showed better anti-bacterial profile as compared to cephalexin and equipotent to ampicillin and amoxicillin on gram-positive bacterial strains. All the derivatives were also screened for anti-TB activity against mycobacterium tuberculosis H37Ra. Among the series, cycloocta-thiophene-tethered cephalexin analog 3c displayed excellent antitubercular activity with MIC values 0.78 mg/ml. Low cytotoxicity and high selectivity index indicate the efficacy of 3c against mycobacterial infections. The results from present study offer a novel approach to modify the existing drug class of ureidopenicillins to yield antimicrobials with promising utility.

Novel 2,4-dimethyl-5-((E)-3-phenyl-3-oxoprop-1-enyl)-1H-pyrrole-3-carboxylic acid derivatives: new leads in cancer and bacterial chemotherapy - Rasal, Nishant K.; Sonawane, Rahul B.; Choudhari, Amit S.; Chakraborty, Shakti S.; Sarkar, Dhiman D.; Jagtap, Sangeeta, V. (ChemistrySelect, 2018)
The efficiently designed and synthesized novel 2,4-dimethyl-5-((E)-3-phenyl-3-oxoprop-1-enyl)-1H-pyrrole-3-carboxylic acid derivatives has been described here which is encouraged by the anticancer activities associated with sunitinib and semaxanib. Synthesized compounds were characterized by (HNMR)-H-1, (CNMR)-C-13 and high-resolution mass spectrometry (HRMS). They are evaluated for invitro antiproliferative properties on cancer cell lines as well as antibacterial activity against gram-positive and gram-negative species. The bioassay results revealed that several compounds exhibit potential antiproliferation activity. Among them, the lead compound 2,2,2-trifluoroethyl 5-((E)-3-(3-fluoro-4-(trifluoromethyl)phenyl)-3-oxoprop-1-enyl)-2,4-dimethyl-1H-pyrrole-3-carboxylate (9g) showed the most potent anticancer activity against MDA-MB-231 and PC-3 cancer cell line with GI(50) values of 5.51 and 5.15 mu g/mL and subsequently more active than sunitinib (GI(50): 6.50 mu g/mL) against PC-3. Same compound 9g also exhibits the most potent antibacterial activity against gram-positive bacteria Bacillus subtilis and Staphylococcus aureus with IC50 of 1.44 and 1.54 mu g/mL. In silico prediction, shows that all seven potent compounds obeyed Lipinski rule for druglikeness. Structure-activity relationship (SAR) study reflect the activity enhance with electron withdrawing group on aryl ring and replacement of acid by its bioisosteres i.e. amide and ester group. These studies have successfully identified many newly synthesized compounds as potential anticancer as well as antibacterial agent for further development.

Rational design of coumarin derivatives as antituberculosis agents - Mali, Hemlata M.; Sabale, Sandip S.; Degani, Mariam S.; Borkute, Rachana; Choudhari, Amit S.; Sarkar, Dhiman; Krishna, Vagolu Siva; Sriram, Dharmarajan (Future Medicinal Chemistry, 2018)
A series of coumarin derivatives was designed as potential antituberculosis agents. Results: The compounds were screened against active and dormant Mycobacterium tuberculosis (Mtb). Compounds 3k and 3n were found to have the most promising activity against replicating MtbH37Rv exhibiting minimum inhibitory concentration of 4.63 and 9.75 mu M respectively. The compounds were also effective against dormant MtbH37Rv exhibiting more potency than the standard drugs, isoniazid and rifampicin. The compounds were found to be non-cytotoxic against human cell lines. Conclusion: This study provides promising antituberculosis agents that are effective against replicating as well as dormant Mtb and can thus act as potential leads for further development.

Synthesis and biological evaluation of novel triazole-biscoumarin conjugates as potential antitubercular and anti-oxidant agents - Danne, Ashruba B. (Research on Chemical Intermediates, 2018)
The synthesis of a new series of triazole-biscoumarin conjugates by using a molecular hybridization approach is described. The newly synthesized compounds 6a–k were evaluated for their in vitro antitubercular activity against active and dormant Mtb H37Ra and anti-oxidant activity against DPPH radical scavenging. Molecular docking simulations for the antitubercular activity showed that the conjugates 6a–k bind in the pocket of the DprE1 enzyme. Most of the conjugates displayed good antitubercular activity against both the active and dormant Mtb H37Ra strain. The compound 6h displayed very good antitubercular activity against dormant Mtb H37Ra with an IC50 value of 1.44 μg/mL. Most of the synthesized conjugates exhibit excellent anti-oxidant activity with an IC50 of less than the standard BHT. Compound 6b is the most active among all the conjugates with an IC50 value of 08.17 ± 0.11 μg/mL. The molecular docking study shows good agreement between the observed antitubercular activity and the binding affinity.
Keywords: 1; 2; 3-triazoles; Anti-oxidant activity; Antitubercular activity; Biscoumarins; Molecular docking

Triazole-diindolylmethane conjugates as new antitubercular agents: synthesis, bioevaluation, and molecular docking - Danne, Ashruba B.; Choudhari, Amit S.; Chakraborty, Shakti; Sarkar, Dhiman; Khedkar, Vijay M.; Shingate, Bapurao B. (MedChemComm, 2018)
We describe the synthesis of novel triazole-incorporated diindolylmethanes (DIMs) using a molecular hybridization approach. The in vitro antitubercular activity of the DIMs against Mycobacterium tuberculosis H37Ra (ATCC 25177) was tested in the active and dormant state. Among all the synthesized conjugates, the compounds 6b, 6f, 6l, 6n, 6q, 6r, and 6s displayed good antitubercular activity against both the active and dormant Mtb H37Ra strain. The compound 6l exhibited good antitubercular activity against dormant Mtb H37Ra with an IC50 value of 1 g mL(-1) and IC90 (MIC) value of 3 g mL(-1). The compounds 6b, 6l, and 6r displayed good antitubercular activity against active Mtb H37Ra with IC50 values of 2.19, 1.52, and 0.22 g mL(-1), respectively. The compounds 6b, 6h, 6l, and 6s displayed more than 70% inhibition against the Gram-positive Bacillus subtilus strain at 3 g mL(-1). The molecular docking study showed the binding modes of the titled compounds in the active site of the DprE1 enzyme and assisted with elucidating a structural basis for the inhibition of Mycobacteria.

Design and synthesis of 2-amino-thiophene-proline-conjugates and their anti-tubercular activity against mycobacterium tuberculosis H37Ra - Baravkar, Sachin B.; Wagh, Mahendra A.; Nawale, Laxman U.; Choudhari, Amit S.; Bhansali, Sujit; Sarkar, Dhiman; Sanjayan, Gangadhar J. (ChemistrySelect, 2019)
The emergence of extensively drug resistant tuberculosis (XDRTB) and multi-drug resistant tuberculosis (MDR-TB) has necessitated the development of new drugs with short chemotherapy treatment regime and cost effectiveness. To overcome these challenges, we are reporting the synthesis of a series of 2-amino-thiophene-proline-conjugates which show potent invino and ex-vivo anti-tubercular (anti-TB) activity against mycobacterium tuberculosis (rntb) H37Ra. The synthesis of these 2-amino-thiophene-proline-conjugates was carried out via solution phase peptide coupling reactions using methyl-2aminothiophene-3-carboxylate 8 as an intermediate obtained by modified gewald reaction. Intermediate 8 was coupled with different amino acids to obtain dipeptides 3, 4, 5, 6a and 7. Priliminary anti-TB assay data encoureaged us to synthesize modified proline derivatives 6b-6k via formation of a benzoxazinone intermediate 16. Most of these conjugates are active against mtb H37Ra in both active (A) and dormant (D) strains. They are also active against drug resistant mtb H37Ra strains. A trifluoroethyl ester analog, 6i was the most potent among the series [MIC 1 mu g/mL] along with 6f and 6g [MIC 2-6 mu g/mL]. Cytotoxicity studies suggested that, these compounds are less cytotoxic to human cell lines HeLa, MCF-7, HUVEC and hence possess high selectivity index (SI). Docking studies revealed that the binding mode of most active compounds 6i, 6g and 6f is in accordance with their bioactivity studies having docking score 8.969, 8.446 and 7.865, respectively. More- over, in sllico ADME properties suggest that all the compounds possess drug like properties.
Keywords: 2-aminothiophene; Anti-tubercular; docking studies; Inh A gene; selectivity index

Synthesis and biological evaluation of 2,4,5-trisubstituted thiazoles as antituberculosis agents effective against drug-resistant tuberculosis - Karale, Uttam B.; Krishna, Vagolu Siva; Krishna, E. Vamshi; Choudhari, Amit S.; Shukla, Manjulika; Gaikwad, Vikas R.; Mahizhaveni, B.; Chopra, Sidharth; Misra, Sunil; Sarkar, Dhiman; Sriram, Dharmarajan; Dusthackeer, V. N. Azger; et al. (European Journal of Medicinal Chemistry, 2019)
The dormant and resistant form of Mycobacterium tuberculosis presents a challenge in developing new anti-tubercular drugs. Herein, we report the synthesis and evaluation of trisubstituted thiazoles as antituberculosis agents. The SAR study has identified a requirement of hydrophobic substituent at C2, ester functionality at C4, and various groups with hydrogen bond acceptor character at C5 of thiazole scaffold. This has led to the identification of 13h and 13p as lead compounds. These compounds inhibited the dormant Mycobacterium tuberculosis H37Ra strain and M. tuberculosis H37Rv selectively. Importantly, 13h and 13p were non-toxic to CHO cells. The 13p showed activity against multidrug-resistant tuberculosis isolates. (C) 2019 Elsevier Masson SAS. All rights reserved.

Phytochemicals in cancer treatment: from preclinical studies to clinical practice (vol 10, 1614, 2020) - Choudhari, Amit S.; Mandave, Pallavi C.; Deshpande, Manasi; Ranjekar, Prabhakar; Prakash, Om (Frontiers in Pharmacology, 2020)
Keywords: Anticancer; clinical; medicinal plants; phytochemicals; preclinical

Phytochemicals in cancer treatment: from preclinical studies to clinical practice - Choudhari, Amit S.; Mandave, Pallavi C.; Deshpande, Manasi; Ranjekar, Prabhakar; Prakash, Om (Frontiers in Pharmacology, 2020)
Cancer is a severe health problem that continues to be a leading cause of death worldwide. Increasing knowledge of the molecular mechanisms underlying cancer progression has led to the development of a vast number of anticancer drugs. However, the use of chemically synthesized drugs has not significantly improved the overall survival rate over the past few decades. As a result, new strategies and novel chemoprevention agents are needed to complement current cancer therapies to improve efficiency. Naturally occurring compounds from plants known as phytochemicals, serve as vital resources for novel drugs and are also sources for cancer therapy. Some typical examples include taxol analogs, vinca alkaloids such as vincristine, vinblastine, and podophyllotoxin analogs. These phytochemicals often act via regulating molecular pathways which are implicated in growth and progression of cancer. The specific mechanisms include increasing antioxidant status, carcinogen inactivation, inhibiting proliferation, induction of cell cycle arrest and apoptosis; and regulation of the immune system. The primary objective of this review is to describe what we know to date of the active compounds in the natural products, along with their pharmacologic action and molecular or specific targets. Recent trends and gaps in phytochemical based anticancer drug discovery are also explored. The authors wish to expand the phytochemical research area not only for their scientific soundness but also for their potential druggability. Hence, the emphasis is given to information about anticancer phytochemicals which are evaluated at preclinical and clinical level.
Keywords: Anticancer; clinical; medicinal plants; phytochemicals; preclinical

Eichhornia crassipes mediated bioinspired synthesis of crystalline nano silver as an integrated medicinal material: a waste to value approach - Moudgil, Aliesha; Deval, Animesh S.; Dharne, Mahesh S.; Sarkar, Dhiman M.; Choudhari, Amit S.; Chaudhari, Bhushan P. (Journal of Cluster Science, 2021)
The present study deals with the synthesis of silver nanoparticles from Eichhornia crassipes. Dynamic light scattering (DLS), Transmission electron microscopy (TEM), UV-Vis spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy and X-ray diffraction (XRD) were performed for nanoparticle characterization. The aqueous plant extract of Eichhornia crassipes was phytochemically analyzed for phenol, flavonoid, reducing sugar content, alkaloids, saponins and carotenoids. The synthesized particles after optimization of important parameters have an average diameter of 12.48 +/- 3.43 nm with a spherical morphology and zeta potential of - 31.53 mV. At 100 mu g/ml of nanoparticle concentration, the antioxidant activity of 93.6% was observed. MIC (Minimum inhibitory concentration) values exhibiting the antimicrobial attributes reported an estimated value of 7.8 mu g/ml for gram-negative and higher values of 31.25 and 250 mu g/ml for gram-positive bacteria. The antibiofilm assay showed 86.89% and 74.7% of the reduction in violacein synthesis and biofilm inhibition respectively at 15 mu g/ml nanoparticle concentration. The anticancer assay reported the IC50 (Inhibitory concentration) values of 13.32, 14.71 and 19.91 mu g/ml for HeLa, HCT 116 and L6 cell lines respectively. Thus the study establishes a significant integrative treatment to combat secondary infections in cancer patients. Graphic
Keywords: antibacterial activity; Antibiofilm activity; Anticancer activity; Antioxidant activity; Eichhornia crassipes; silver nanoparticles